Reactive wetting in corrosion: A mild steel example - Ng, L.; Fung, C.; Connor, J.; Ngothai, Y.; Druskovich, D.; Sedev, Rossen (2012)
Wettability is a key factor in various engineering, scientific and industrial processes. The contact angle is the most common measure of the degree to which a liquid wets a solid surface. However, most investigations of contact angles focus on rather ideal systems where liquids wet inert, smooth, and homogeneous surfaces which rarely exist in the real world. Reactive wetting occurs when the liquid reacts with the solid (as in corrosion) and has received much less attention. While the wetting principles remain unchanged, in time the chemical reactions affect the composition and properties of the three-phase system. The influence of chemical kinetics is further complicated by the effects of mass transport. We have examined the corrosion of mild steel under a small aqueous droplet (basic, neutral or acidic). In order to correlate the corrosion process with the wettability of the metal surface, electrochemical measurements of the corrosion rate were combined with contact angle measurements. We show how wettability is affected by corrosion and, at the same time, the local corrosion rate is modified by the conditions imposed by the fixed volume of the droplet and its evaporation. These findings are relevant for the performance of tools and engineering structures subjected to water spraying or under condensation-evaporation conditions. Copyright © (2012) by the Australasian Corrosion Association.